Analysis of Ring Compression Test by Upper Bound Theorem as Special Case of Non-symmetric Part. (2015) - Moncada, A.; Martín, F.; Sevilla, L.; Camacho, A.M.; Sebastián, M.A.
Abstract: The ring compression test is considered one of the most reliable ways to obtain the friction shear factor existing in a plastic deformation process, particularly in open die forging processes. The test is performed on a ring-shaped specimen, so that the whole workpiece is axisymmetric. The application of the upper bound theorem with a triangular rigid zones model was initially developed with regard to plane strain and symmetrical geometric configurations. In this paper, the application to the ring faces consider that the neutral radius that defines the reversal of the flow of the material establishes two areas of different section and therefore the possibility of addressing the study considering not symmetrical sections.